An analysis on power quality measurement and monitoring techniques for nonlinear load - Shahrul Ashikin, Azmi; Mohd Rafi, Adzman; Mohd Fayzul, Mohammed; Siti Rafidah, Abdul Rahim; Zainuddin, Mat Isa; Ismail, Daut, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2008 organized by Malaysian Technical Universities Network (MTUN) comprising of Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussain Onn Malaysia (UTHM), Universiti Teknikal Malaysia (UTeM) and Universiti Malaysia Pahang (UMP), 15th - 16th March 2008 at Putra Palace, Perlis, Malaysia.